Sustainable encapsulation of bio-active agents and microorganisms in electrospun nanofibers: A comprehensive review - Masillamani, A K A; Sabarinathan, K G; Gomathy, M; Kumutha, K; Prasanthrajan, M; Kannan, J; Aishwarya, P (Plant Science Today, 2025)
Nanotechnology is a technological discipline focused on the design, fabrication and utilization of structures, systems and devices through the manipulation of atoms and molecules at the nanoscale. A significant advancement in this field is the development of a nanocarrier system for microbe encapsulation using electrospun nanofibers. These nanofibers, characterized by their diameters in the nanometric range, are produced through nanotechnology. The electrospinning technique is a versatile method that fabricates these nanofibers from polymer solutions, including polyvinyl alcohol (PVA), polyvinyl pyrrolidone (PVP), polyethylene oxide (PEO), polyethylene glycol (PEG) and chitosan, using high voltage. Nanofibers play a crucial role in various fields, including environmental remediation, medicine, agriculture and textiles. Beneficial microorganisms are microbial cells that aid crops by protecting them from pathogens, supplying essential nutrients and alleviating both biotic and abiotic stresses. Several techniques have been developed to encapsulate microorganisms within nanofibers, with electrospinning being the most widely applied method. This technique effectively traps microbial cells while preserving their viability for extended periods without causing harm. Microorganisms such as bacteria, fungi and viruses, as well as fertilizers, pesticides and growth hormones, can be successfully encapsulated within nanofibers. This review provides a comprehensive overview of nanofibers, including their characterization, the polymers utilized [such as chitosan, PVA, PEO, PEG and alginate] and the electrospinning process with its variations. It also discusses techniques for encapsulating microbial cells within nanofibers and their current applications in agriculture.